RESIDUAL EFFECT OF ETOFENPROX (TREBON 20% WP) AS A NEW INSECTICIDE ON DIFFERENT SURFACES IN SOUTH OF IRAN - H. Ladonni; M. Motabar (Iranian Journal of Public Health, 1995)
The residual activity and air-borne efficacy of Etofenprox (trebon 20% WP) were studied on different surfaces in hut scale trial, in Kazeroun south of Iran, in 1992. The bio-assay contact mortality tests with trebon against Anopheles stephensi showed similar responses on pluster, cement and mud surfaces (except wooden surfaces), i.e. at 250, 400 and 500 mg/m2, trebon had residual activity for about 75 to 82, 95 and 110 days respectively. On wooden surfaces, trebon showed longer residual activity than the latter surfaces, i.e. at 250, 400 and 500 a.i. mg/m2 , trebon had residual activity for 90, 110 and 127 days respectively. Fumigation test with trebon at different rates of application showed no remarkable effect on An.stephensi. Based on the results of this study, trebon at 500, 400 and 250 mg/m2 had a residual activity for about 4, 3 and 2.5 months on different surfaces and hence the recommended dosages for continuation study could be 500 and 250 mg/m2 in a large scale trial in south of Iran.